Assessment Report, Mkom District, Bamenda Division, Cameroons Province (Colonial Letters and the Contact of Knowledges, 1927)
This file contains colonial assessment report and memoranda on Mkom District, Bamenda Division
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies